2007
DOI: 10.1517/14712598.7.11.1739
|View full text |Cite
|
Sign up to set email alerts
|

Anti-IgE in allergic asthma and rhinitis: an update

Abstract: Allergic asthma and rhinitis imposes a huge burden in terms of treatment costs, productivity loss and hospital admissions. IgE plays a significant role in the manifestation of these conditions and the identification of a monoclonal antibody that binds to IgE provides clinicians another therapeutic strategy in the management of these conditions. Blocking the effects of IgE by omalizumab, a recombinant humanized monoclonal antibody that selectively binds to IgE has been shown to be a useful adjunct in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…It also decreases the expression of FcERI on dendritic/mast cells in the nasal mucosa, thereby reducing the nasal allergic response [85]. In placebo-controlled trials, administration of omalizumab resulted in a reduction in symptoms and medication scores of more than 50% [94][95][96][97]. Treatment with omalizumab improves the quality of life in patients with seasonal allergic rhinitis [98].…”
Section: Current and Future Developmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It also decreases the expression of FcERI on dendritic/mast cells in the nasal mucosa, thereby reducing the nasal allergic response [85]. In placebo-controlled trials, administration of omalizumab resulted in a reduction in symptoms and medication scores of more than 50% [94][95][96][97]. Treatment with omalizumab improves the quality of life in patients with seasonal allergic rhinitis [98].…”
Section: Current and Future Developmentsmentioning
confidence: 99%
“…Treatment with omalizumab improves the quality of life in patients with seasonal allergic rhinitis [98]. The medication is particularly effective when used as an adjunct in the treatment of patients with coexisting asthma [96,99,100]. It has been shown that the combination of omalizumab with subcutaneous immu-notherapy is superior to each single treatment alone [96,97].…”
Section: Current and Future Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 35% of patients, the time-to-onset of anaphylaxis was within 30 min of injection, but 5% had a delayed onset of reaction of .24 h. Out of 23 patients, 18 (78%) had a recurrence of anaphylaxis when re-challenged with omalizumab [62]. Therefore, omalizumab should be administered (according to a recent medication guide released by the Food and Drug Administration) in healthcare settings where anaphylaxis can be managed, and patients should be observed for an appropriate time following each injection [63][64][65]. Although omalizumab is well tolerated, its potential long-term side-effects need careful monitoring.…”
Section: Safety Profile Of Omalizumabmentioning
confidence: 99%
“…1,2 Omalizumab is a recombinant humanized monoclonal anti-IgE antibody that binds to the Fc region of the IgE molecule and prevents IgE from interacting with high-or lowaffinity IgE receptors (FceR1 and FceR11), resulting in a reduction of circulating free IgE. 3,4 Omalizumab also down-regulates FceR1 receptors in circulating basophils, mast cells, and circulating antigen-presenting cells; this is believed to result in the down-regulation of inflammatory responses mediated by helper T cells. 4,5 Basophil, mast cell, and particularly eosinophil degranulation play a central role in allergic asthma that occurs in the presence of high IgE levels.…”
mentioning
confidence: 99%